(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Cooperative learning (CL) is recognized under the aspect of valuable instructional approach in nursing education, fostering collaboration, critical thinking, and teamwork skills among students. Objective: To probe the perception and experience of CL in nursing education across the perspectives of nursing instructors. Methodology: A qualitative study was conducted at nursing institutes in Karachi. Seven Nursing Instructors were selected through purposive sampling technique and data collection was continued until thematic saturation was reached, at the point the sample size was deemed sufficient and data collection was stopped. Semi-structured interviews stayed accompanied by discovering the experiences, views, and observations concerning the application of CL strategies in nursing courses. Thematic analysis explored multiple crucial subjects associated with effectiveness, benefits, encounters, and best practices of CL in nursing education. Results: The findings indicates that cooperative learning is perceived as highly effective by instructors, leading to increased student engagement, collaboration, and the improvement of societal abilities. Additionally, the absence of administrative pressure allows instructors the freedom to implement cooperative learning strategies that best meet the needs of their students. Conclusion: The findings offer valuable insights for curriculum design, instructive practices, and faculty development initiatives in nursing education.